Capitalism-Culture and Educational Praxis A Long Revolution - Gitlin, Andrew (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book focuses on educational praxis-connecting work inside schools with work outside school-to produce a revitalized critical theory of education that shows its slide away from Marxism and toward culturalism. The chapters outline a knowledge production process in three connected parts: a critical history; conceptual extensions; and praxis. .
Chapter 1: Becoming Academic: The Construction of Political Bias -- Chapter 2: A Critical History of ECT: From Marxism to Culturalism -- Chapter 3: Finding Capitalist and Cultural Connections: Marx & Others -- Chapter 4: The Oneness of Capitalism and Culture within ECT -- Chapter 5: Marxist Praxis -- Chapter 6: Extended Praxis within ECT -- Chapter 7: That Can't Be Here Done or Can It?.
Keywords: Teaching; Education -- Philosophy; Schools; Marxian school of sociology; Social justice; Pedagogy; Educational Philosophy; School and Schooling; Marxist Sociology; Social Justice